Over a million students use our free study notes to help them with their homework
First complete the square on the curve in the answer to obtain y=(x+2)2 - 5 Now if you were to call your original equation y=f(x) you could see that the new equation is simply y=f(x+2) - 5This ...
Here we need to use the product rule in order to differentiate as we have two functions involved that are being multiplied together. Therefore we use the formula:dy/dx = u dv/dx + v du/dxFirst let u=(x^2 ...
x2 +6x +11this is a quadratic so we try to factorise it. x2 +6x can be turned into (x+3)2 -9 and we plus the 11 from the beginning so the final answer should look like (x+...
(1) y-3x+2=0(2) y2-x-6x2=0Using (1): y=3x-2Sub y value into (2): (3x-2)2-x-6x2=0Expand the brackets: 9x2-13x+4-x-6xAnswered by Phoebe A. • Maths tutor7177 Views
cos(4x) = cos(2(2x)) = 2(cos^2(2x)) - 1 = 2 (cos^2(x) - 1)^2 - 1 = 8(cos^4(x)) - 8(cos^2(x)) + 1
←
287
288
289
290
291
→
Internet Safety
Payment Security
Cyber
Essentials